2022
DOI: 10.1111/1460-6984.12811
|View full text |Cite
|
Sign up to set email alerts
|

Com‐mens: a home‐based logopaedic intervention program for communication problems between people with dementia and their caregivers — a single‐group mixed‐methods pilot study

Abstract: Background: Communication difficulties are common in people with dementia, and often present from an early stage. However, direct treatment options for people with dementia that positively influence their daily communication are scarce.Aims: To evaluate the potential impact and feasibility of a personalized logopaedic intervention. Methods & Procedures:A total of 40 community-dwelling persons with dementia and their caregivers were recruited. Five experienced speech and language therapists (SLTs) delivered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Additionally, some carers improved their ‘communication’ during follow-up, through family or formal support. Therefore, ‘communication’ is potentially modifiable when behaviour problems, especially apathy, occur, and can be further enhanced by therapy that focuses on improving skills and coping with language and communication difficulties in dyads ( Olthof-Nefkens et al, 2022 ). A one-year follow-up of people with Alzheimer’s disease and their carers suggested that relationships were ‘dynamic co-constructions’, built from daily interactions ( Graham & Bassett, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some carers improved their ‘communication’ during follow-up, through family or formal support. Therefore, ‘communication’ is potentially modifiable when behaviour problems, especially apathy, occur, and can be further enhanced by therapy that focuses on improving skills and coping with language and communication difficulties in dyads ( Olthof-Nefkens et al, 2022 ). A one-year follow-up of people with Alzheimer’s disease and their carers suggested that relationships were ‘dynamic co-constructions’, built from daily interactions ( Graham & Bassett, 2006 ).…”
Section: Discussionmentioning
confidence: 99%